Effet des métaux lourds (Cuivre et Zinc) sur les paramètres morpho-physiologiques et biochimiques chez la fève (Vicia faba L.) - ABDELSADOK, Nardjess; KAMMOUN, Ikram (My University, 2018)
Heavy metal pollution has become a real problem threatening our ecosystem, with adverse effects on crop production and biodiversity. The aim of our work is to study separately the influence of copper and zinc in the form of sulphates (Cu So₄ and Zn So₄) at different doses of 100,300 and 500ppm of copper and 300, 500 and 700ppm of zinc, on the biometric, physiological and biochemical behavior of the bean (Vicia faba L.). The application of copper and zinc was carried out during the entire physiological cycle of the plant. The study of the effect of heavy metals (copper and zinc) the elongation of the roots, revealed that it exerts a slowdown and a decrease in the growth of the latter at doses of 100,300 and 500 ppm for copper and 300,500 and 700 ppm for zinc, the elongation of the roots is very sensitive to the increase of copper and decreases in the doses 100, 300 and 500 ppm, however the zinc with the concentration 300 ppm stimulates the elaboration of the length of the roots and beyond 500ppm it becomes toxic. Regarding the physical and chemical parameters, the accumulation of the two metals (copper and zinc) in each of the aerial and root parts of the plant increases as their size increases in the substrate which will cause an increase in the rate of proline and a decrease for the physiological parameter such as the relative water content.
Keywords: métaux lourds; stress; cuivre; zinc; Vicia faba L.; paramètre morphologique; paramètre biochimique.; heavy metals; copper; morphological parameter; biochemical parameter.